Continuous chemical redistribution following amorphous-to-crystalline structural ordering in a Zr-Cu-Al bulk metallic glass. (28th February 2022) - Wu, Xuelian; Lan, Si; Li, Xiyang; Yang, Ming; Wu, Zhenduo; Wei, Xiaoya; He, Haiyan; Naeem, Muhammad; Zhou, Jie; Lu, Zhaoping; Gilbert, Elliot Paul; Ma, Dong; et al.
Highlights: Crystallization kinetics of Zr45.5 Cu45.5 Al9 bulk metallic glass was investigated. Simultaneous DSC and SANS was applied to study in situ the crystallization process. A three-stage structural evolution during crystallization was revealed. Continuous chemical redistribution following structural ordering was observed. A new feature, i.e., the transition region, was identified and discussed. Abstract: Bulk metallic glasses (BMGs) are thermodynamically metastable. As such, crystallization occurs when a BMG is thermally annealed at a temperature above the glass transition temperature. While extensive studies have been performed on the crystallization kinetics of BMGs, most of them have focused on the amorphous-to-crystalline structural ordering, and little attention has been paid to chemical distribution and its relationship with the structural ordering during the crystallization process. In this paper, a new approach, with simultaneous differential scanning calorimetry (DSC) and small angle neutron scattering (SANS) measurements, was applied to study in situ the crystallization of a Zr45.5 Cu45.5 Al9 BMG upon isothermal annealing at a temperature in the supercooled liquid region. Quantitative analysis of the DSC and SANS data showed that the structural evolution during isothermal annealing could be classified into three stages: (I) incubation; (II) amorphous-to-crystalline structural ordering; (III) continuous chemical redistribution. This finding was validated by composition analysis with atom probe tomography (APT), which further identified a transition region formed by expelling Al into the matrix. The transition region, with a composition of (Cu, Al)50 Zr50, served as an intermediate step facilitating the formation of a thermodynamically stable crystalline phase with a composition of (Cu, Al)10 Zr7 . Graphical abstract: Image, graphical abstract